Vitamin D supplementation – still a subject of debate - Vlad Dima; George Iancu; Roxana-Elena Bohiltea; Leonard Nastase; Adrian Ioan Toma; Valentin-Nicolae Varlas; Ana-Maria Davitoiu (Romanian Journal of Medical Practice, 2022)
Vitamin D is a standard vitamin supplementation for children in many countries, used mainly for preventing rickets. Many studies were published about the efficiency of vitamin D administration in children and adults for other pathologies besides rickets. Very often the results were contradictory, but nevertheless, more and more articles are published on this matter. There is no consensus for the effective vitamin D dosage nor for the vitamin D normal serum values. Both vitamin D deficiency and vitamin intoxication are dangerous for children. Recently some studies are showing controversial data that advise being more careful in prescribing vitamin D as a routine.